Marriage, divorce, and children's adjustment - Emery, Robert E.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 1999)
In this completely rewritten second edition, the author uses his family systems model to integrate research findings into a theoretical whole and to evaluate psychological interventions with divorcing and divorced families.
Previous ed.: 1988.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Children of divorced parents -- Mental health; Adjustment (Psychology) in children; Families -- Psychological aspects; Electronic books